2011
DOI: 10.1152/ajpheart.00445.2010
|View full text |Cite
|
Sign up to set email alerts
|

The role of mitosis in LDL transport through cultured endothelial cell monolayers

Abstract: Cancel LM, Tarbell JM. The role of mitosis in LDL transport through cultured endothelial cell monolayers. Am J Physiol Heart Circ Physiol 300: H769 -H776, 2011. First published December 17, 2010 doi:10.1152 doi:10. /ajpheart.00445.2010 have previously shown that leaky junctions associated with dying or dividing cells are the dominant pathway for LDL transport under convective conditions, accounting for Ͼ90% of the transport. We (8) have also recently shown that the permeability of bovine aortic endothelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 49 publications
1
40
0
Order By: Relevance
“…Traction forces between cells and between the cell and substrate were larger on stiffer substrates, so that substrate stiffening promotes gap formation between ECs, thus disrupting the overall monolayer cohesion (25). Such stiffness-dependent changes of endothelium integrity would play a central role in atherosclerotic lesion and plaque development since leaky junctions within the EC monolayer are highly correlated with increased permeability to LDL transport (5).…”
Section: Discussionmentioning
confidence: 99%
“…Traction forces between cells and between the cell and substrate were larger on stiffer substrates, so that substrate stiffening promotes gap formation between ECs, thus disrupting the overall monolayer cohesion (25). Such stiffness-dependent changes of endothelium integrity would play a central role in atherosclerotic lesion and plaque development since leaky junctions within the EC monolayer are highly correlated with increased permeability to LDL transport (5).…”
Section: Discussionmentioning
confidence: 99%
“…Weinbaum et al (1985) hypothesized that leaky junctions around cells in a state of apoptosis or mitosis provide the major pathway for transport of large molecules such as LDL across the endothelium. More recent studies have shown a strong correlation between apoptosis and mitosis rates and LDL permeability of endothelial monolayers in culture (Cancel & Tarhell 2010, 2011). These studies, and others (reviewed in Tarbell 2003, 2010), suggest that chronic differences in shear stress do affect LDL transport into the vessel wall and that low shear stress may be expected to increase LDL permeability.…”
Section: Arterial Fluid Mechanics and Vascular Diseasementioning
confidence: 99%
“…LDL particles, which are carried with blood flow in the lumen, may attach to the endothelial cell surface via LDL receptors and then can be transferred to the subendothelial layer by vesicles through the process of vesicular transcytosis. However, the portion of LDL passage via this mechanism is under 10%, in contrast to over 90% of LDL particles passing through cellular leakage which is formed by the detachment of endothelial cells [7,9,10]. Higher detachment rates are caused by elevated apoptosis and mitosis of cells under low or oscillatory WSS conditions, often referred to as "disturbed flow."…”
Section: (B)mentioning
confidence: 99%
“…Leaky junctions are formed by the detachment of adjacent endothelial cells due to apoptosis and mitosis of the cell. The role of leaky junctions has been demonstrated in in vitro experiments [9,10] where an endothelial cell layer was coated on a porous medial structure. When an increase of apoptosis and mitosis rate was induced, it was found that the volume flux of blood plasma and solute flux of LDL increased linearly with the rate of endothelial cell apoptosis and mitosis.…”
Section: Introductionmentioning
confidence: 99%